Zika virus infects pericytes in the choroid plexus and enters the central nervous system through the blood-cerebrospinal fluid barrier - Kim, Jihye; Alejandro, Brian; Hetman, Michal; Hattab, Eyas M.; Joiner, Joshua; Schroten, Horst; Ishikawa, Hiroshi; Chung, Dong-Hoon (PLoS pathogens, 2020)
Zika virus (ZIKV) can infect and cause microcephaly and Zika-associated neurological complications in the developing fetal and adult brains. In terms of pathogenesis, a critical question is how ZIKV overcomes the barriers separating the brain from the circulation and gains access to the central nervous system (CNS). Despite the importance of ZIKV pathogenesis, the route ZIKV utilizes to cross CNS barriers remains unclear. Here we show that in mouse models, ZIKV-infected cells initially appeared in the periventricular regions of the brain, including the choroid plexus and the meninges, prior to infection of the cortex. The appearance of ZIKV in cerebrospinal fluid (CSF) preceded infection of the brain parenchyma. Further the brain infection was significantly attenuated by neutralization of the virus in the CSF, indicating that ZIKV in the CSF at the early stage of infection might be responsible for establishing a lethal infection of the brain. We show that cells infected by ZIKV in the choroid plexus were pericytes. Using in vitro systems, we highlight the possibility that ZIKV crosses the blood-CSF barrier by disrupting the choroid plexus epithelial layer. Taken together, our results suggest that ZIKV might exploit the blood-CSF barrier rather than the blood-brain barrier to invade the CNS.
Gesehen am 03.09.2020